Soil Enzyme Activities and Their Relationship to Total Soil Bacteria, Soil Microbial Biomass and Soil Chemical Characteristics of Organic and Conventional Farming - Aziz, Muhammad Abdul; Hazra, Fahrizal; Salma, Selly; Nursyamsi, Dedi (UNIVERSITY OF LAMPUNG, 2018)
Soil properties such as physical, chemical, biological, microbiological and biochemical aspects affect on soil quality. Soil microbiological activities directly affect stability of ecosystems and soil fertility. The research aimed to determine soil microbial activities through soil enzyme activities and their relationship to total soil bacteria, soil microbial biomass, and soil chemical characteristics. The research was conducted at Laboratory of Soil Microbiology, Indonesian Soil Research Institute, Bogor from July 2015 to January 2016. Soil samples 0-10 cm depth were taken from organic and conventional farming of some commodities (tomato, carrot, maize, broccoli) from Bogor Regency, while those of rice were taken from Tasikmalaya Regency. Soil dehydrogenase, urease and cellulase activities were determined using some modified methods. The results showed that soil dehydrogenase and cellulase activities in organic farming were higher than those in conventional farming, whereas the soil urease activity in organic farming was lower than that in conventional farming. The total soil bacteria and soil microbial biomass were significantly and positively correlated with soil dehydrogenase, urease, and cellulose activities. Soil dehydrogenase, urease, and cellulose activities were very significantly and positively correlated with all soil characteristics tested, i.e. soil organic C, total N, potential P and K, available P and K, CEC, and pH, except that soil urease activity was very significantly and negatively correlated with soil pH. The results of this research indicated that organic farming is recommended for maintaining soil fertility and plant productivity; however, small use of urea fertilizer is still needed in the farming.